PERAN MAHASISWA EKONOMI DAN BISNIS ISLAM DALAM MENDUKUNG UMKM MELALUI INTEGRASI LOKASI BISNIS DI GOOGLE MAPS - Hamidatus Shalihah; Siti Aisyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the role of students from the Faculty of Economics and Islamic Business (FEBI) in supporting the development of Micro, Small, and Medium Enterprises (UMKM) through the integration of business locations on Google Maps.. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation of UMKM that are assisted and FEBI students involved in the assistance activities. The results show that the assistance of FEBI students in creating and verifying Google Business Profiles, optimizing digital content, and managing customer reviews can increase business visibility, ease of customer access, and consumer trust in UMKM. Students act as educators, facilitators, digital consultants, promoters, and researchers in the process of empowering UMKM based on digital technology. The conclusion of this study confirms that the integration of Google Maps through student mentoring is an effective and applicable strategy in increasing the competitiveness and sustainability of UMKM in the digital era.